Inside the FDIC : thirty years of bank failures, bailouts, and regulatory battles - Bovenzi, John F. (Hoboken, New Jersey : Wiley, 2015)
'Banks are held out as symbols of stability, safe places to put your money. Yet since the early 1980's over 3,400 banks have failed, an average of about two a week for a period exceeding thirty years. These bank failures aren't steady, regular, and easily predictable events. Periods of calm and tranquility have been followed by chaos; booms have led to busts, and peaceful complacency often has turned into sudden devastation. This book will provide a different view of the FDIC and other bank regulators. Readers will see: How an agency that had become almost invisible would emerge as a major and highly independent force impacting U.S. financial markets. How nine FDIC Chairmen, each with different strengths and weaknesses, helped shape the FDIC and the U.S. financial regulatory system. How conflicts between the FDIC and other financial regulatory agencies unfolded amid the pressures and challenges associated with bank failures and financial crises. This book dives into the chaos surrounding bank failures to show firsthand what happens to those individuals and businesses caught in the storm'--
Includes index.
Includes bibliographical references and index.
Keywords: Deposit insurance -- United States; Bank failures -- United States; Banks and banking -- Government policy -- United States; Banks and banking -- State supervision -- United States